The given equation is Ax + By = C.
(a) To find the x intercept, let y = 0. To find a y intercept, let x = 0.
When we evaluate the expression when y = 0, we get the x-intercept, when we evaluate the expression when x = 0, we get the y-intercept.
(b) Let's evaluate the expression to find the x-intercept of the line.
![\begin{gathered} Ax+B(0)=C \\ Ax=C \\ x=(C)/(A) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6dhgy94qsb7a4kf291vnr2f0paa5uxdlda.png)
The x-intercept of the line is (C/A, 0).
(c) Let's evaluate the expression to find the y-intercept of the line. (x = 0).
![\begin{gathered} A(0)+By=C_{} \\ By=C \\ y=(C)/(B) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8va1xzkb6x520uddbcyrzb96zomgr79i50.png)
The y-intercept of the line is (C/B, 0).